Deep brain stimulation for pantothenate kinase‐associated neurodegeneration: A meta‐analysis. Issue 2 (11th January 2019) - De Vloo, Philippe; Lee, Darrin J.; Dallapiazza, Robert F.; Rohani, Mohammad; Fasano, Alfonso; Munhoz, Renato P.; Ibrahim, George M.; Hodaie, Mojgan; Lozano, Andres M.; Kalia, Suneil K.
Abstract: Background: Pantothenate kinase‐associated neurodegeneration is a rare autosomal‐recessive disorder, characterized by progressive neurodegeneration associated with brain iron accumulation. DBS has been trialed to treat related movement disorders, particularly dystonia. The objective of this study was to determine the outcome and safety of DBS for pantothenate kinase‐associated neurodegeneration. Methods: We performed a meta‐analysis using independent participant data (n = 99) from 38 articles. Primary outcome was change in movement and disability scores of the Burke‐Fahn‐Marsden Dystonia Rating Scale 1 year postoperatively. Secondary outcomes were response rate and complications. Results: Patients with classic‐type (n = 58) and atypical‐type (n = 15) pantothenate kinase‐associated neurodegeneration were operated on at a median age of 11 and 31 years, respectively ( P < 0.001). GPi was primarily targeted (n = 87). Mean dystonia movement score improved 1 year following GPi‐DBS (‐26%; 95% confidence interval, ‐37% to ‐15%), particularly in atypical versus classic cases (‐45% vs ‐16%; P < 0.001). At least 30% improvement was observed in 34% of classic versus 73% of atypical cases ( P = 0.04). Higher preoperative score and atypical type predicted larger improvement. GPi‐DBS improved dystonia disability score in atypical (‐31%; 95% confidence interval, ‐49% to ‐13%) but not classic (‐5%; 95% confidence interval, ‐17% to 8%) cases. Prevalence of surgical infections (6%) and hardware failure (7%) was similar to other dystonia etiologies. Two patients died within 3 months. There was insufficient data to describe outcome > 1 year following GPi‐DBS or with other DBS targets. Overall, small sample sizes limited generalizability. Conclusions: This meta‐analysis provides level 4 evidence that GPi‐DBS for pantothenate kinase‐associated neurodegeneration may improve dystonia movement scores in classic type and atypical type and disability scores in atypical type 1 year postoperatively. © 2019 International Parkinson and Movement Disorder Society